2021
DOI: 10.1007/s00436-020-07033-3
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne zoonoses and commonly used diagnostic methods in human and veterinary medicine

Abstract: Around the world, human health and animal health are closely linked in terms of the One Health concept by ticks acting as vectors for zoonotic pathogens. Animals do not only maintain tick cycles but can either be clinically affected by the same tick-borne pathogens as humans and/or play a role as reservoirs or sentinel pathogen hosts. However, the relevance of different tick-borne diseases (TBDs) may vary in human vs. veterinary medicine, which is consequently reflected by the availability of human vs. veterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 126 publications
(170 reference statements)
0
10
0
Order By: Relevance
“…Because they are obligate hematophagous ectoparasites and feed on diverse vertebrate hosts, they are considered as one of the most important vectors of zoonotic pathogens. Ticks can transmit a wide variety of bacteria, parasites and viruses 1 3 . In human and veterinary medicine, most tick-borne pathogens are transmitted by various hard ticks belonging to genera Ixodes, Haemaphysalis, Dermacentor, Hyalomma and Rhipicephalus and by certain soft ticks belonging to genera Argas and Ornithodoros.…”
Section: Introductionmentioning
confidence: 99%
“…Because they are obligate hematophagous ectoparasites and feed on diverse vertebrate hosts, they are considered as one of the most important vectors of zoonotic pathogens. Ticks can transmit a wide variety of bacteria, parasites and viruses 1 3 . In human and veterinary medicine, most tick-borne pathogens are transmitted by various hard ticks belonging to genera Ixodes, Haemaphysalis, Dermacentor, Hyalomma and Rhipicephalus and by certain soft ticks belonging to genera Argas and Ornithodoros.…”
Section: Introductionmentioning
confidence: 99%
“…It was also found that Dermacentor reticulatus ticks were carriers of Francisella tularensis and Francisella spp. (Michelet et al, 2013;Springer et al, 2021). There is currently no data on the possibility of leukemia virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The transmission of some diseases was already proved by E.N. Pavlovsky when he explored the biology and ecology of I. ricinus in the Novgorod province (Sivkov et al, 2009;Springer et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
“…Ixodes ricinus is not only the most common tick species (even in dogs) in Central Europe, but also the vector of numerous pathogens such as Anaplasma phagocytophilum, Borrelia spp., Rickettsia spp., tick-borne encephalitis virus, and other, less common pathogens such as Francisella tularensis and, potentially, Coxiella burnetii , as well as members of the genus Babesia spp. [ 6 , 7 , 8 , 9 ]. Dermacentorreticulatus is, most notably, a carrier of Babesia canis , the causative agent of canine babesiosis [ 7 ].…”
Section: Introductionmentioning
confidence: 99%